The Influence of Taxpayer Awareness, Tax Sanctions, and the Level of Understanding of Taxpayers on Individual Taxpayer Compliance at KPP Pratama Gianyar - DWIPASARI, Made Sukma; PUTRA, I Made Wianto; KAWISANA, Putu Gede Wisnu Permana (Journal of Governance, Taxation and Auditing, 2023)
This study entitled The Effect of Taxpayer Awareness, Tax Sanctions, and the Level of Understanding of Taxpayers on Individual Taxpayer Compliance at KPP Pratama Gianyar. The problems studied in this study are: how is the influence of taxpayer awareness, tax sanctions, and the level of partial understanding of taxpayers on individual taxpayer compliance at KPP Pratama Gianyar. This study aims to determine the awareness of taxpayers, tax sanctions, and the level of partial understanding of taxpayers on individual taxpayer compliance at KPP Pratama Gianyar. The research sample is 100 respondents. The primary data collection was carried out using a questionnaire. The data analysis technique used is multiple linear regression. The results of this study show that there is a positive and significant effect partially from taxpayer awareness, tax sanctions, and the level of understanding of taxpayers on individual taxpayer compliance at KPP Pratama Gianyar.